Perbedaan Kadar Asam Urat pada Penderita Hipertensi dengan Diabetes Melitus Tipe 2 dan tanpa Diabetes Melitus Tipe 2 di Rumah Sakit Umum Daerah Dr. Sayidiman Magetan - MAULANA, YUDRIK (2016)
Background: The increasing levels of uric acid plays an important role in the morbidity of patients with hypertension. DM is a common comorbid hypertensive patients. Objective: To know the distinction of uric acid levels in hypertensive patients with type 2 diabetes mellitus and without diabetes mellitus type 2 in Dr. Sayidiman Hospitals Magetan. Methods: Researchers conducted an observational analytic research with cross sectional study design. Subjects were hypertensive patients with type 2 diabetes mellitus and without tipe 2 diabetes mellitus in Dr. Sayidiman Hospitals. The sampling technique performed in consecutive sampling. Data were obtained from medical records of patients from January 2012 to June 2015. Statistical analysis used independent T test. Results: This study used 54 sample, consists of 27 patients in the group of hypertension with type 2 diabetes mellitus and 27 patients in the group of hypertensive without type 2 diabetes mellitus. The difference between the mean levels of uric acid in hypertension with type 2 diabetes mellitus group 6.559 ± 2.2560 mg/dl compared with hypertension without type 2 diabetes mellitus group 4.922 ± 1.3051 mg/dl with p = 0.002. Conclusions: There was distinction of uric acid levels in hypertensive patients with type 2 diabetes mellitus and without type 2 diabetes mellitus.